Analisis Gaya Bahasa Dalam Lirik Lagu “Hati-Hati di Jalan” Karya Tulus: (Kajian Stilistika) - Galih Lintang Asmarandhana; Elsa Nabila Putri; Heppy Latifatun Nisa; Elita Irandani; Ahmad Hadafi; Eni Nurhayati (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This research discusses the analysis of language style in the lyrics of the song “Hati-Hati Di Jalan” by Tulus with a stylistic study. The reason the author chose this song is 1) The song lyrics have a language style that can be studied, 2) So that listeners know the meaning of the song they are listerning to, 3) The song lyrics can also be used as teaching material for Indonsian language subjects. The problems formulations of this research is “What is the language style of the lyrics of the song Hati-Hati Di Jalan by Tulus?” The research method used is descriptive qualitative with note-taking techniques. Based on the research result, there are three types of language found in song lyrics, including comparative figures of speech, affirmative figures of speech, and satirical figures of speech.